USMLE step 2 clinical skills triage : a guide to honing clinical skills - Schwechten, Kevin (Oxford University Press, 2010)
USMLE Step 2 Clinical Skills Triage is the indispensable preparation book for the Step 2 Clinical Skills exam, presenting 40 high-yield patient-encounter cases that simulate the examination experience. Cases are organized for straightforward learning: a sample dialogue that mimics actual doctor-patient communication is followed by guidelines on performing the physical exam, ending the case, writing the patient note, and outlining the differential diagnosis. Comprehensive yet succinct, the cases address almost all possible exam scenarios, including telephone cases and "difficult patient & qu